SISTEM KONTROL OTOMATIS PENGISIAN CAIRAN DAN PENUTUP BOTOL MENGGUNAKAN ARDUINO UNO Rev 1.3 - Sonny Rumalutur; Serli Liling Allo (LPPM Poltek ST Paul, 2019)
The system design test results are obtained that when the sensor detects an object with a certain distance, the sensor will issue a signal to the micro which is then forwarded to the charging driver circuit to turn on the relay. The relay functions as a switch or switch that will fill the liquid in the bottle, when the driver is charging on, the process of filling the liquid occurs in the bottle, and the micro filling process issues a signal in the active motor driver circuit. The conveyor driver is active after giving a signal from Arduino Uno, the conveyor will stop after the sensor detects a bottle then stops, and the micro sends a signal to turn the motor driver down on the bottle cap to close the bottle on. When the bottle closing process is complete the motor driver backs up actively moving the road conveyor back. The percentage error of theoretical value and measurement of the difference is small and when filling the liquid in a bottle takes 17 seconds until the bottle is fully filled and by using the micro, the liquid filler on the bottle and the bottle cover can be completed properly.